2017
DOI: 10.1002/anie.201706070
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Organic Luminescent Centers in Sol–Gel‐Synthesized Yttrium Aluminum Borate Matrix Leading to Bright Visible Emission

Abstract: Yttrium aluminum borate (YAB) powders prepared by sol-gel process have been investigated to understand their photoluminescence (PL) mechanism. The amorphous YAB powders exhibit bright visible PL from blue emission for powders calcined at 450 °C to broad white PL for higher calcination temperature. Thanks to C labelling, NMR and EPR studies show that propionic acid initially used to solubilize the yttrium nitrate is decomposed into aromatic molecules confined within the inorganic matrix. DTA-TG-MS analyses show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…These a-YAB micrometer-sized powders prepared by modified Pechini and sol-gel methods give intense visible emissions with potential for developing metal ion-free luminescent materials, particularly phosphors for solid-state lighting. [4][5][6] Such intense visible luminescence has also been reported in many other inorganic materials obtained by various wet-chemical routes. [7][8][9][10][11] During the synthesis process, the metal-organic precursors undergo a complex chain of reactions, including polyesterification (Pechini route) or polycondensation (sol-gel chemistry) reactions for the preparation of initial resins or gels, followed by degradation and the associated structural transformation during the thermal treatments performed under controlled atmospheric conditions (pyrolysis or calcination).…”
Section: Introductionsupporting
confidence: 59%
See 4 more Smart Citations
“…These a-YAB micrometer-sized powders prepared by modified Pechini and sol-gel methods give intense visible emissions with potential for developing metal ion-free luminescent materials, particularly phosphors for solid-state lighting. [4][5][6] Such intense visible luminescence has also been reported in many other inorganic materials obtained by various wet-chemical routes. [7][8][9][10][11] During the synthesis process, the metal-organic precursors undergo a complex chain of reactions, including polyesterification (Pechini route) or polycondensation (sol-gel chemistry) reactions for the preparation of initial resins or gels, followed by degradation and the associated structural transformation during the thermal treatments performed under controlled atmospheric conditions (pyrolysis or calcination).…”
Section: Introductionsupporting
confidence: 59%
“…In an earlier report, we identified the presence of certain organic compounds confined in the a-YAB matrix using solidstate NMR and EPR spectroscopies. 4 The pulsed-ENDOR associated DFT calculations revealed that the small (2-3 rings) PAH molecules exhibit good correlation with the PL properties of a-YAB powders. 4 The electronic structures and S-S/S-T excitation energies of these small PAH molecules are calculated here using TD-DFT methods (ESI, † Table S1).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations